A novel bismuth hydroxide (Bi(OH)3) semiconductor with highly-efficient photocatalytic activity. Issue 59 (4th July 2022) - Liu, Sitong; Ren, Guangmin; Gao, Xinyu; Li, Zizhen; Wang, Liang; Meng, Xiangchao
Abstract : In this research, a novel Bi(OH)3 photocatalyst was successfully synthesized with excellent activity in both photocatalytic CO2 reduction and phenol decomposition. Abstract : Herein, a novel Bi(OH)3 photocatalyst was successfully synthesized. Benefiting from the suitable band positions, abundant alkaline groups and oxygen vacancies, the as-prepared semiconductor exhibits efficient activity in both photocatalytic CO2 reduction with a CO production rate of 36 μmol g −1 h −1 and phenol decomposition with a 92.7% degradation rate in 180 min.